International consensus statement on nomenclature and classification of the congenital bicuspid aortic valve and its aortopathy, for clinical, surgical, interventional and research purposes. (22nd July 2021) - Michelena, Hector I; Della Corte, Alessandro; Evangelista, Arturo; Maleszewski, Joseph J; Edwards, William D; Roman, Mary J; Devereux, Richard B; Fernández, Borja; Asch, Federico M; Barker, Alex J; Sierra-Galan, Lilia M; De Kerchove, Laurent; et al.
Abstract: This International Consensus Classification and Nomenclature for the congenital bicuspid aortic valve condition recognizes 3 types of bicuspid valves: 1. The fused type (right-left cusp fusion, right-non-coronary cusp fusion and left-non-coronary cusp fusion phenotypes); 2. The 2-sinus type (latero-lateral and antero-posterior phenotypes); and 3. The partial-fusion (forme fruste) type. The presence of raphe and the symmetry of the fused type phenotypes are critical aspects to describe. The International Consensus also recognizes 3 types of bicuspid valve-associated aortopathy: 1. The ascending phenotype; 2. The root phenotype; and 3. Extended phenotypes.